(untitled) (LEARNing Landscapes, 2009)
In this paper I review my use of arts-based research practices as a set of pedagogical tools for teaching media literacy in an undergraduate sociology course titled "Images & Power: Popular Culture." The paper details how I incorporated arts-based research into my course as a part of my holistic and participatory approach to media literacy. Arts-based practices are an effective tool for fostering critical consciousness. Samples of student work are included.